2015
DOI: 10.7287/peerj.preprints.554v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

CheckM: assessing the quality of microbial genomes recovered from isolates, single cells, and metagenomes

Abstract: Large-scale recovery of genomes from isolates, single cells, and metagenomic data has been made possible by advances in computational methods and substantial reductions in sequencing costs. While 25 this increasing breadth of draft genomes is providing key information regarding the evolutionary and functional diversity of microbial life, it has become impractical to finish all available reference genomes. Making robust biological inferences from draft genomes requires accurate estimates of their completeness a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
487
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 443 publications
(560 citation statements)
references
References 0 publications
2
487
0
Order By: Relevance
“…Potential contaminant sequences were removed using PRODEGE (Tennessen et al, 2015). The completeness of the genomes within bins was then estimated by counting universal single copy genes using CHECKM (Parks et al, 2014). Binning was also manually curated based on guanine cytosine content, top blast hits and mate pairings.…”
Section: Genomic Assembly Binning and Annotationmentioning
confidence: 99%
“…Potential contaminant sequences were removed using PRODEGE (Tennessen et al, 2015). The completeness of the genomes within bins was then estimated by counting universal single copy genes using CHECKM (Parks et al, 2014). Binning was also manually curated based on guanine cytosine content, top blast hits and mate pairings.…”
Section: Genomic Assembly Binning and Annotationmentioning
confidence: 99%
“…The relatively small but largely complete draft genome recovered from the enrichment culture consists of 1,753,479 nucleotides with a GC content of 36.6%. Analysis of the sequence bin using checkM software (Parks et al, 2015) indicated low level of contamination (2.2%) that is likely from a very similar strain (strain heterogeneity of 100%). One complete rRNA operon (5S, 16S and 23S) and a second copy of the 23S rRNA gene have been identified.…”
Section: Genome Properties and Mechanisms For Syntrophymentioning
confidence: 99%
“…Draft genomes were recovered from metagenomic contig datasets using a binning approach based on tetranucleotide frequency with Vizbin (Laczny et al, 2015). Draft genomes were manually curated and genome quality and taxonomy were assessed using Phylopythia (McHardy et al, 2007) and CheckM using the taxonomy_wf command with at least order level specific marker gene sets (Parks et al, 2015). Ribosomal RNA genes in assembled contigs and recovered draft genome bins were predicted using RNAmmer and SSU_Finder from CheckM (Lagesen et al, 2007;Parks et al, 2015).…”
Section: Metagenomic Binning and Annotationmentioning
confidence: 99%
“…Draft genomes were manually curated and genome quality and taxonomy were assessed using Phylopythia (McHardy et al, 2007) and CheckM using the taxonomy_wf command with at least order level specific marker gene sets (Parks et al, 2015). Ribosomal RNA genes in assembled contigs and recovered draft genome bins were predicted using RNAmmer and SSU_Finder from CheckM (Lagesen et al, 2007;Parks et al, 2015). Phylogenetic analysis based on extracted 16S rRNA gene sequences was performed using CLC workbench version 8.5.1.…”
Section: Metagenomic Binning and Annotationmentioning
confidence: 99%